Theoretical investigation on the adsorption and diffusion of lithium-ion on and between graphene layers with size and defect effects - Yan-Zi Yu; Jian-Gang Guo; Li-Jun Zhou (Adsorption Science & Technology)
Adsorption and diffusion of lithium-ion on and between graphene layers are investigated by an analytical model, employing a pairwise potential, which can be approximated by the Lennard–Jones potential to express the interaction between lithium-ion and each carbon atom of graphene. The equilibrium position and binding energy of lithium-ion at three particular adsorption sites (hollow, bridge, and top) are calculated, and the adsorption stability is discussed. The results show that hollow site is the most stable adsorption site, and top site is the most unstable. The adsorption and diffusion of lithium-ion on different sizes of monolayer graphene are investigated and proved to be size and edge dependent. Moreover, lithium-ion would rather diffuse on the surface of graphene than through a hexagonal carbon ring to the other side no matter what the graphene sheet size is. In addition, two kinds of vacancy defects in graphene are considered to study the diffusion of lithium-ion. The vacancy defect can improve energy barrier, and if a vacancy defect is big enough, lithium-ion migrating through the vacancy area from one layer to another is feasible. The possible applications of present study include rechargeable lithium-ion graphene battery and Li storage in carbon material.